Quality Consideration for e-Learning System Based on ISO/IEC 25000 Quality Standard - Aedah, Abd Rahman (2020)
—e-Learning is defined as the use of information and communication technology (ICT) to support learning. eLearning has been used widely in the world. However, the extensive use of e-Learning requires a proper quality design approach. This paper investigates the use of quality standards and frameworks in the implementation of e-Learning system. Analysis is performed on quality evaluation effort based on standard which has been validated and accepted at International level. The analysis suggests that there is a possibility of an e-Learning project development to be assessed based on criteria from ISO/IEC standard in order to produce quality software product. Initially, the concept of quality and several existing standards for e-Learning system are discussed. In addition, an overview on ISO/IEC 25000 series is presented. The characteristics and sub-characteristics related to ISO/IEC 25000 are described. The research outlined in this paper shows that software product quality is essential in e-Learning project. The research outcome is to determine key quality evaluation criteria based on ISO/IEC 25000 for e-Learning systems. This standard supports building quality into software product.